2014
DOI: 10.3810/pgm.2014.05.2771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HMG-CoA Reductase Inhibitors on Leptin-Induced Endothelial Cell Proliferation, Migration, and Capillary-Like Tube Formation

Abstract: Through modulation of prenylation, leptin-induced pro-atherosclerotic events including proliferation and migration were inhibited by HMG-CoA reductase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Many studies have already shown the application potentials of magnesium and its alloy as biodegradable implants, such as bone fixation, cardiovascular stent, surgical staples and microclip [ [7] , [8] , [9] , [10] , [11] , [12] ]. The biofunctions of magnesium have also been proved such as stimulating bone growth, promoting angiogenesis and wound healing [ [13] , [14] , [15] ]. Wu et al found good biocompatibility and no inflammation of pure magnesium staples that were implanted in stomach of pigs for 9 weeks [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already shown the application potentials of magnesium and its alloy as biodegradable implants, such as bone fixation, cardiovascular stent, surgical staples and microclip [ [7] , [8] , [9] , [10] , [11] , [12] ]. The biofunctions of magnesium have also been proved such as stimulating bone growth, promoting angiogenesis and wound healing [ [13] , [14] , [15] ]. Wu et al found good biocompatibility and no inflammation of pure magnesium staples that were implanted in stomach of pigs for 9 weeks [ 4 ].…”
Section: Introductionmentioning
confidence: 99%